Jangha (wall) of the Suswani Mata Temple facing South - Temples of India Project Team (Jio Institute, 2024)
Seen here is the jangha (wall) of the Suswani Mata Temple facing South. On the bhadra (central offset) is an in situ sculpture of Ganesha, framed in deep decorative niches. This image is flanked by two attendants on the intermediary projections and dikapalas (gods of the cardinal directions) on the corner projections of the wall. The devakosthas (niches) on the central and corner projections have small vyala (mythical composite figures) on the brackets.